2017
DOI: 10.1111/cge.12956
|View full text |Cite
|
Sign up to set email alerts
|

Association of the missense variant p.Arg203Trp in PACS1 as a cause of intellectual disability and seizures

Abstract: Graphical abstract Graphical abstract key: Wt: weight, Ht: height, OFC: open fontanelle, DD: developmental delay, ID: intellectual disability, EEG: electroencephalogram, OCD: obsessive compulsive disorder, ADHD: attention deficit hyperactivity disorder, ASD: atrial septal defect, VSD: ventricular septal defect, PDA: patent ductus arteriosis, PFO: patent foramen ovale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 5 publications
0
31
0
Order By: Relevance
“…Ataxia due to cerebellar hypoplasia, dyspraxia, and stereotypic movements had been reported with the PACS1 mutation (Schuurs-Hoeijmakers et al, 2016;Stern et al, 2017). In Patient 1, trihexyphenidyl hydrochloride altered her movement characteristics.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Ataxia due to cerebellar hypoplasia, dyspraxia, and stereotypic movements had been reported with the PACS1 mutation (Schuurs-Hoeijmakers et al, 2016;Stern et al, 2017). In Patient 1, trihexyphenidyl hydrochloride altered her movement characteristics.…”
mentioning
confidence: 89%
“…Information Table). To our knowledge, 28 patients with a recurrent de novo PACS1 mutation (c.607C > T) have been reported mainly in Western populations (Pefkianaki et al, 2018;Schuurs-Hoeijmakers et al, 2016;Stern et al, 2017); however, the recurrent mutation has never been reported in Asian countries. Brain MRI at 4 months showed no abnormality.…”
mentioning
confidence: 93%
“…It is now known that the average case is a product of many susceptibility-increasing variations. Only a handful of ASD-related diseases have monogenic causes, such as Rett syndrome, fragile X syndrome, tuberous sclerosis, and Schuurs–Hoeijmakers syndrome (Artuso et al, 2011; Stern et al, 2017; Woodbury-Smith and Scherer, 2018). Dozens of large-scale genetic studies have since been conducted on ASD patients and their families, leading to hundreds of risk genes being identified.…”
Section: Genetics Of Asdmentioning
confidence: 99%
“…PACS1 and PACS2 are two human paralogous genes that each cause a distinctive human disorder. A specific class of mutations in PACS1 , that is, c.607C > T p.(Arg203Trp) and c.608G > A p.(Arg203Gln), results in Schuurs‐Hoeijmakers syndrome (OMIM #615009), characterized by intellectual disability and facial dysmorphism (Dutta, 2019; Hoshino et al, 2019; Pefkianaki et al, 2018; Schuurs‐Hoeijmakers et al, 2012; Schuurs‐Hoeijmakers et al, 2016; Stern et al, 2017). Meanwhile, a specific class of mutations in PACS2 , that is, c.625G > A p.(Glu209Lys) and c.631G > A p.(Glu211Lys), causes early infantile epileptic encephalopathy 66 (EIEE 66) (OMIM #618067) (Olson et al, 2018; Terrone et al, 2020).…”
Section: Introductionmentioning
confidence: 99%